Optimizing efforts to restore aquatic ecosystem connectivity requires thinking beyond large dams. (22nd December 2021) - Baumgartner, Lee J; Marsden, Tim; Duffy, Deanna; Horta, Ana; Ning, Nathan
Abstract: Infrastructure-induced fragmentation of riverine ecosystems has engendered the need for more effective aquatic restoration efforts globally. Fragmentation assessments have been extensively undertaken to inform connectivity restoration efforts for fish and other aquatic biota, but they have potentially underestimated the extent of fragmentation by fixating on large dams and overlooking the contribution of other barriers like road crossings and small irrigation structures. The current study addresses this limitation in Mekong region countries (MReCs) of Southeast Asia, by assessing the fragmentation impacts of road crossings and small irrigation structures together with large dams. Our analysis indicates that the basin-scale fragmentation impact of road crossings is similar to that of large dams in MReCs, while small irrigation structures actually have a far greater impact. These findings raise concerns about the real global extent of aquatic fragmentation, and highlight the need for decision-makers to think beyond dams when attempting to restore connectivity for aquatic biota.